Swiss army man [videorecording (DVD)] - Radcliffe, Daniel, 1989-; Dano, Paul, 1984-; Winstead, Mary Elizabeth (2016)
Hank is stranded on a deserted island, having given up all hope of ever making it home again. One day everything changes when a corpse names Manny washes up onshore. The two become fast friends, and ultimately go on an epic adventure that will bring Hank back to the woman of his dreams.